2020
DOI: 10.3390/electronics9121996
|View full text |Cite
|
Sign up to set email alerts
|

A Low-Cost Digital Pulsed Coherent Spectrometer for Investigation of NQR in Layered Semiconductor GaSe and InSe Crystals

Abstract: A low-cost digital pulsed nuclear quadrupole resonance (NQR) radio-spectrometer is proposed, all main modules of digital processing and synthesis of which on the field-programmable gate array (FPGA) are implemented. The input sensitivity of the device is of the order of 3 μV to 5 μV which allows conducting NQR studies in samples of relatively small dimensions. The application of the developed methods of NQR pulsed radio spectroscopy made it possible to increase spectral resolution, improve spectral shape and s… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
7
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
4
2

Relationship

1
5

Authors

Journals

citations
Cited by 6 publications
(7 citation statements)
references
References 21 publications
0
7
0
Order By: Relevance
“…We already successfully developed an FPGA-based pulse sequence shaper for the NQR portable sensor [ 19 ]. In [ 21 ], we considered the implementation of a cheap digital pulse coherence spectrometer for the study of NQR in GaSe- and InSe-layered semiconductor crystals. We made some modifications to the structure of the pulsed single-coil coherent NQR observation method, which led to the following improvements: By implementing the pulsed mode of the transistor bias control, the power consumption of the RF transmitter is reduced by almost 50%, and can now operate in pulsed modes (up to 30 ms) even without active cooling, while maintaining the output power up to 1 kW.…”
Section: Basic Structure Of An Nqr Sensormentioning
confidence: 99%
See 1 more Smart Citation
“…We already successfully developed an FPGA-based pulse sequence shaper for the NQR portable sensor [ 19 ]. In [ 21 ], we considered the implementation of a cheap digital pulse coherence spectrometer for the study of NQR in GaSe- and InSe-layered semiconductor crystals. We made some modifications to the structure of the pulsed single-coil coherent NQR observation method, which led to the following improvements: By implementing the pulsed mode of the transistor bias control, the power consumption of the RF transmitter is reduced by almost 50%, and can now operate in pulsed modes (up to 30 ms) even without active cooling, while maintaining the output power up to 1 kW.…”
Section: Basic Structure Of An Nqr Sensormentioning
confidence: 99%
“…As a hardware base for the implementation of the proposed configuration structure, we used the motherboard of a pulsed NQR sensor ( Figure 7 a), the operating principle of which is described in detail in [ 21 , 31 ]. The core of the motherboard is an FPGA EP4CE15E22C8, the internal structure of which contains more than 15,000 logic gates.…”
Section: Hardware Implementation and Experimentsmentioning
confidence: 99%
“…This study is a continuation of a number of our applied studies in the field of NQR spectroscopy, which revealed the need to improve the parameters of the preamplifier for the NQR pulse Fourier spectrometer 2 . Being an integral component of an NQR spectrometer, such an amplifier assumes a critical role -amplification of ultraweak signals with an amplitude of a few microvolts emitted by atomic nuclei in response to radiofrequency irradiation 3,4 . To achieve the desired effect, we chose the scheme of parallel amplification of weak signals, using several operational amplifiers (opamps) working in tandem.…”
Section: Introductionmentioning
confidence: 99%
“…For the rapid search of explosives and narcotic substances in non-metallic containers and hand luggage, which mostly contain crystalline nitrogen atoms, the method of NQR pulse spectroscopy of the 14N isotope with fast Fourier transformation in the low-frequency region of the short-wave frequency range of 0.5 MHz to 5 MHz is effectively used 1,2 . When detecting small concentrations of such substances, the main requirements for monitoring equipment are high sensitivity of the radio receiving path (units of microvolts) and high power of excitation pulses (about 1 kW) 3,4 . The latter leads to increased requirements for the radio frequency transmitter of the NQR radio spectrometer, in particular, an increase in its efficiency, increased reliability and energy characteristics, which is especially important in a portable version of the design 5 .…”
Section: Introductionmentioning
confidence: 99%